PERBEDAAN KOMPETENSI IPA FISIKA MELALUI PENILAIAN PORTOFOLIO DALAM PEMBELAJARAN MODEL KREATIF-PRODUKTIF BERKELOMPOK DENGAN INDIVIDUAL SISWA KELAS VIII SMP NEGERI 25 PADANG - Devi Susanti (PILLAR OF PHYSICS EDUCATION, 2013)
Abstract - This study aimed to investigate the differences in physical competencies through portfolio assessment of the teaching between groups and individual creative-productive model with the eighth grade students in SMP 25 Padang. Type of research is quasi-experimental with the study design randomized control group only design. Sampling was conducted using cluster random sampling technique. The competence data collected by using portfolios, pencil and paper test, observation sheets attitudes and performance scoring rubric. The data analysis technique competency in pencil and paper test and portfolio is two equality average test (t test) at the level 0.05, while for the attitude and performance by calculating the average value of each indicator of competence. Based on the results obtained are significant difference in the competence of science Physics through portfolio assessment of the teaching between groups and individual creative-productive model with the eighth grade students in SMP 25 Padang. The results of t-test analysis of the written test, obtained thitung = 2.103 and ttable = 2.00 at real level of 0.05. The results of t-test analysis of the portfolio, acquired thitung = 1.38 and ttable = 2.00. In the assessment of attitudes and performance appraisal average values ​​obtained experimental class 1 higher than the experimental class 2. Overall the experimental class 1 better than the experimental class 2. Keywords: portfolio assesment, creative-productive, groups, individual, attitudes assesment, performance